2021
DOI: 10.1111/dmcn.15066
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in quality and safety outcomes for hospitalized children with intellectual disability

Abstract: To investigate if there are inequities in quality and safety outcomes for children with intellectual disability admitted to two tertiary paediatric hospitals.METHOD A cross-sectional study of 1367 admissions for 1018 randomly selected patients admitted for more than 23 hours to one of two tertiary children's hospitals in Sydney, Australia (1st January-31st December 2017). Electronic medical records were manually interrogated to identify children with intellectual disability (including developmental delay). Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 40 publications
5
25
0
2
Order By: Relevance
“…: 2019/ETH00367). 9 We found almost 14% of admissions were for a child or young person with intellectual disability or developmental delay. Furthermore, these children had a longer median length of stay, cost of admission and were over-represented in the reported clinical incident data.…”
Section: Introductionmentioning
confidence: 81%
“…: 2019/ETH00367). 9 We found almost 14% of admissions were for a child or young person with intellectual disability or developmental delay. Furthermore, these children had a longer median length of stay, cost of admission and were over-represented in the reported clinical incident data.…”
Section: Introductionmentioning
confidence: 81%
“…In Australia, 4.5% of children aged 15 years or under have intellectual disability (Australian Bureau of Statistics, 2018). A recent study found almost 14% of admissions to a tertiary paediatric healthcare organization were CYP with intellectual disability (Mimmo et al, 2021). These CYP also had more frequent admissions, a significantly longer median length of stay, and higher median cost of admission than their peers (Mimmo et al, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A recent study found almost 14% of admissions to a tertiary paediatric healthcare organization were CYP with intellectual disability (Mimmo et al, 2021). These CYP also had more frequent admissions, a significantly longer median length of stay, and higher median cost of admission than their peers (Mimmo et al, 2021). At the same time, inpatient CYP with intellectual disability and their parents consistently report poor quality and safety experiences.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of admissions to Sydney Children’s Hospitals Network in 2017 for children aged 0–18 years found that 13.9% of admissions greater than 23 h involved a child or AYA with intellectual disability [ 20 ]. In addition, 8% of cancer-related admissions in the sample were for children with intellectual disability [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%